2010
DOI: 10.1002/cbic.201000192
|View full text |Cite
|
Sign up to set email alerts
|

Fluorous Iminoalditols: A New Family of Glycosidase Inhibitors and Pharmacological Chaperones

Abstract: A collection of new reversible glycosidase inhibitors of the iminoalditol type featuring Nsubstituents containing perfluorinated regions has been prepared for evaluation of physicochemical, biochemical and diagnostic properties. The vast variety of feasible oligofluoro moieties allows for modular approaches to customised structures according to the intended applications, which are influenced by the fluorine content as well as the distance of the fluorous moiety from the ring nitrogen. The first examples, in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 84 publications
0
55
0
Order By: Relevance
“…102 Although the maximum increase was achieved at a concentration of 500 mM, similar to that found for DGJ, in all single experiments the presence of DLHex-DGJ at 20 mM concentration was sufficient to yield more than 10% of the normal control mean activity, which was proposed as the critical level for normal substrate turnover. The minimal concentration of chaperone necessary to reach this threshold in homozygous R201C fibroblasts was further reduced to 5 mM for the fluorous derivative 62 103,104 and to only 1 mM for the long-chain dansylated N-alkyl-DGJ derivative 63. 105 Mahuran and coworkers reported a similar result for N-nonyl-DGJ (NN-DGJ, 64; Fig.…”
Section: Glycomimetic-based Pcs For G M1 -Gangliosidosismentioning
confidence: 96%
“…102 Although the maximum increase was achieved at a concentration of 500 mM, similar to that found for DGJ, in all single experiments the presence of DLHex-DGJ at 20 mM concentration was sufficient to yield more than 10% of the normal control mean activity, which was proposed as the critical level for normal substrate turnover. The minimal concentration of chaperone necessary to reach this threshold in homozygous R201C fibroblasts was further reduced to 5 mM for the fluorous derivative 62 103,104 and to only 1 mM for the long-chain dansylated N-alkyl-DGJ derivative 63. 105 Mahuran and coworkers reported a similar result for N-nonyl-DGJ (NN-DGJ, 64; Fig.…”
Section: Glycomimetic-based Pcs For G M1 -Gangliosidosismentioning
confidence: 96%
“…Next, we wanted to introduce a reporter group to allow subsequent mass spectrometric monitoring of reactions by introducing a heavy substituent, in particular a nonafluoro- tert -butoxy group ( Scheme 4 ) [ 58 ]. Therefore, diethylenoxy benzoic acid methyl ester 36 was synthesised as described previously from methyl hydroxybenzoate ( 21 ) and 2-(2-chloroethoxy)ethanol [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chaperone candidates for human b-gal were also explored in the derivatives of DGJ (taBle 2) [48][49][50]. Recently, Rigat et al reported that N-nonyl-DGJ (NN-DGJ) enhanced mutant b-gal activity in feline G M1 -gangliosidosis fibroblasts.…”
Section: Other Chaperone Candidates For Human B-galmentioning
confidence: 97%
“…Chaperones for Gaucher and Pompe diseases have also been tested in preclinical studies. In addition, synergetic effect of Yes (model mice) [32][33][34][35][36][38][39][40] DGJ, NB-DGJ R201C, R201H, R457Q ND [32] Galactose R442Q ND [72] DLHex-DGJ R201C, R201H, C230R, G428E ND [48] Fluorous iminoalditols R148S, R201C, D332N ND [49] NN-DNJ R201H, W509C, R483P (feline GLB1) ND [50] 6S-NBI-DGJ (MTD118) 24 out of 88 missense mutations (including I51T, R201C, G438E)…”
Section: Future Perspectivementioning
confidence: 98%